Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.1002/tl.20292
|View full text |Cite
|
Sign up to set email alerts
|

Student Engagement with Community

Abstract: Student engagement in the local community comes with both risks and rewards. This chapter explains the cognitive, behavioral, and affective outcomes of student learning in the community, along with noting the importance of preparation and reflection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(16 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…For example, the work integrated with learning in healthcare settings supports and stimulates the provision of high quality, therefore meeting the current and future care needs of individuals (Pennbrant & Svensson 2018 :191). Community engagement needs vigilant planning, communication and organisation (Knight-McKenna et al 2018 :72). This is to ensure that activities are successful and that people participate fully.…”
Section: Findings and Discussionmentioning
confidence: 99%
“…For example, the work integrated with learning in healthcare settings supports and stimulates the provision of high quality, therefore meeting the current and future care needs of individuals (Pennbrant & Svensson 2018 :191). Community engagement needs vigilant planning, communication and organisation (Knight-McKenna et al 2018 :72). This is to ensure that activities are successful and that people participate fully.…”
Section: Findings and Discussionmentioning
confidence: 99%
“…Specifically focusing on actual experiences with families and individuals in communities makes a difference [ 24 ]. Research has shown that student engagement with the community and SLP, or any other type of community-based participation, provides a space for academic knowledge and skill and challenges to be applied and tested during learning [ 25 ]. Over the three years studied, this cohort of medical students found it a privilege to give and take many lessons from the experiences and opportunities in the medical school’s SL program.…”
Section: Discussionmentioning
confidence: 99%
“…Cycle 1 data revealed possible causes for students to not fully engage in community service work and provided a framework for co-constructing more engaged community services experiences in Cycle 2.The literature and research process were informed by a focus on Selfdetermination and motivation (Baeten, 2013;Cheon & Reeve, 2020;Conley & French, 2014;Curren, 2020;Ryan & Deci, 2017;DeRoberts & Bland, 2018;Noble-Carr, 2014;Murray, 2014;Paixão & Gamboa, 2016;Reeve & Haulsic, 2009;Rönkkö & Lepistö, 2016;Snodin, 2012;Stefanou et al, 2004) community action (Houser, 2016;Jones, 2017, Knight-McKenna, 2018; and collaboration and relationships (Courela, 2014;Jacobson, 2011;Jia et al, 2016;McHugh, 2018;Payne, 2013;Sanders, 2018). A review of the following literature on student motivation and success combined with the findings of Cycle 1 imply the need for developing a student driven and co-created learning process may gather important findings regarding self-determination in alternative school settings.…”
Section: Discussionmentioning
confidence: 99%
“…Engagement related to community service can increase skills in self-determination (Knight-McKenna, 2018). This theme is perhaps the richest in data, and provides evidence of a research design incorporating autonomy, relatedness, and competency and impacting a student's self-identity and purpose.…”
Section: Self-determinationmentioning
confidence: 94%
See 1 more Smart Citation